Evaluation of the implementation of the ward based outreach teams (WBOT) programme in a rural area:the case of the Kgetleng sub-district, North West province - Mulelu, Rodney Azwinndini (My University, 2016)
The Ward Based Outreach Teams (WBOT) Programme is established in South Africa as part of a series of strategies to strengthen Primary Health Care (PHC) and to improve service delivery in the country. The purpose of the study was to gain an understanding of the experiences of Community Health Workers (CHW) in the implementation of the WBOT programme. The objectives of the study were to evaluate the experiences of CHWs in the WBOT, to evaluate factors that facilitate the implementation and to make recommendations and strategies on what can be done to improve the WBOT programme. A quantitative research design was used where self-administered questionnaires were provided to respondents for data collection. Respondents were asked to complete the questionnaires; completed questionnaires were returned by only 12 of the 27 respondents, resulting in a 44% response rate. The study’s findings indicate that the Community Health Workers (CHWs) regarded the WBOT as helping the community in many ways such reducing the long queues at the clinic and providing the care of the patients in their own homes, although concerns about poor participation by the community structures and nurses in the health facilities were expressed. CHWs expressed experiences that were positive and negative when conducting their work in the community. The results from the study have shown that there are successes, challenges and lesson learned. The results of the study further indicated that the programme is being implemented well even though it is still in a pilot phase in the sub-district. The programme has managed to improve and save many lives in the communities of Kgetleng Sub-district. Despite the level of depth in this study, there is a crucial need for more for more in-depth research regarding the experiences of users of the WBOT services and to conduct similar studies looking into urban areas and to compare and contrast the rural and urban findings.
Thesis (MBA.) --University of Limpopo, 2016
Keywords: Ward based outreach teams; Community health workers; Community participation; Health; District health system; Health care team; Community health aides